2021
DOI: 10.1080/23311886.2021.1970880
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Interdisciplinary Research in the Digital Era: Obstacles and Perspectives of Collaboration in Social and Data Sciences - An Empirical Study

Abstract: In the last decade, a transition in research design and methodology is identified in social research methodology; however, the high entry threshold (i.e., technical knowledge) to utilize computational methods and the ethical concerns seem to slow down the process. A possible way out is that social sciences collaborate with computational or data scientists in interdisciplinary research projects to rely on each other's skills and to develop jointly accepted ethical principles. In this exploratory study, we colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
(58 reference statements)
0
4
0
2
Order By: Relevance
“…Darknet research implementation requires researchers to consider data validity issues appearing on digital platforms (for a summary, see Parti & Szigeti, 2021), in this case specifically, the issue formulated by online anonymity. Despite the prevention methods applied by Dark0de Reborn, bots could register and add invalid data to product descriptions or user reviews.…”
Section: Limitationsmentioning
confidence: 99%
“…Darknet research implementation requires researchers to consider data validity issues appearing on digital platforms (for a summary, see Parti & Szigeti, 2021), in this case specifically, the issue formulated by online anonymity. Despite the prevention methods applied by Dark0de Reborn, bots could register and add invalid data to product descriptions or user reviews.…”
Section: Limitationsmentioning
confidence: 99%
“…La puesta en marcha de proyectos de investigación en la época actual también supone el conocimiento de cómo gestionar la información y las posibilidades del intercambio de datos para beneficio de la comunidad académica e incluye, por lo tanto, el encuentro con múltiples complicaciones y dificultades que implican, la realización de Ciencia Abierta en todas sus fases, un desafío (Fressoli & Arza, 2018). Del mismo modo, en la actualidad empieza a formar parte de algunos requisitos de agencias de investigación, financiación o requisito de revistas y comités evaluadores precisamente la disposición pública de los datos (Logan et al, 2021;Van Dijk et al, 2021) y, por lo tanto, se presta cada vez más relevante las investigaciones con equipo multidisciplinares en los que puedan colaborar hacia procesos más éticos y transparentes sin que los conocimientos técnicos sean en sí mismo el mayor problema (Parti & Szigeti, 2021).…”
Section: Implicaciones Hacia La Ciencia Abiertaunclassified
“…13 (2022), 138-156 Juan José Sosa y Manuel Area ~ 150 ~ ética del proceso investigador, relevante en el campo de la Tecnología Educativa y en la Ciencia Abierta. Desarrollar estrategias más éticas y transparentes en el ámbito de la Ciencia Abierta y de la Tecnología Educativa implica el trabajo conjunto y colaborativo en distintos campos disciplinares que permita dar respuesta a las complejidades inherentes al campo educativo y del tratamiento de datos e información (Parti & Szigeti, 2021;. Además, dentro de la investigación en Tecnología Educativa, las GAN pueden aportar la técnica que permita la reutilización, el intercambio y la difusión de información, recursos digitales y conjuntos de datos sobre nuestra línea que nos permita la toma de decisión hacia una transformación digital alineada con los principios de la Ciencia Abierta, es decir, más accesible, colaborativa y en beneficio de la sociedad (Alhadad et al, 2018;Bethencourt-Aguilar et al, 2021ayb;Alés, 2020).…”
Section: Discusión Y Conclusionesunclassified
“…Through literature cross-referencing, it is found that management research is more often cited from social science literature than other disciplines (Neeley, 1981). Through contextual knowledge extraction, Parti and Szigeti (2021) found that the citation of gamification techniques influences the dynamics of urban development research and the revision of scientific research directions.…”
Section: Introductionmentioning
confidence: 99%